Local implementation of the Family Health Program in Brazil A implementação do Programa Saúde da Família no cenário local - Rosana Magalhães; Mônica de Castro Maia Senna (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2006)
This article discusses the implementation of the Family Health Program in the municipalities of Camaragibe, Aracaju, São Gonçalo, and the Federal District of Brazil, aiming to identify possible interfaces between the program's shaping and different incentives structures, the local health system's case-resolving capacity, experiences with social participation, and accountability mechanisms. The article shows that aspects related to the constitution of local health systems in terms of the quantitative and qualitative supply of services, technical and management training within the Municipal Health Department, investment in other levels of care, and local political traditions are crucial variables for understanding the diversity of experiences in the implementation of the Family Health Program. Este trabalho busca discutir a implementação do Programa Saúde da Família (PSF) nos municípios de Camaragibe, Aracaju, São Gonçalo e Distrito Federal, de forma a identificar as possíveis interfaces entre a conformação do programa e as diferentes estruturas de incentivo, resolubilidade do sistema local de saúde, experiências de participação social e mecanismos de accountability constituídos. O estudo demonstrou que aspectos relacionados à constituição do sistema local de saúde em termos da oferta quantitativa e qualitativa dos serviços, capacitação técnico-gerencial no âmbito das Secretarias Municipais de Saúde, investimento nos outros níveis de atenção e a tradição política local são variáveis cruciais para a compreensão da diversidade de experiências de implementação do PSF.